Suksesi dan hubungan orang tua-anak dalam bisnis keluarga (studi kasus pada sentra batik trusmi Cirebon) - Abdurokhim, Abdurokhim; Rahayu, Agus; Dirgantari, Puspo Dewi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Family business is a business that is run jointly by family members. The purpose of this study is to determine the succession process and the relationship between parents and children in the family business precisely in the Trusmi Cirebon batik center. The method used is qualitative with data collection techniques through interviews, documentation and observation of four informants or sources namely Batik Ninik Ichsan, Batik EB, Batik Katura, and Batik Trusmi. The results of the research on Batik Ninik Ichsan, Batik Trusmi, Batik Katura, and Traditional Batik EB found that the succession process carried out was unplanned, but the parents provided mentoring to make batik at school age, except for Batik Trusmi who only learned it after marriage. In the aspect of parent-child relationship, it is known that Batik Ninik Ichsan, Batik Trusmi, and Batik Katura are in a good relationship because there is no pressure on their children to participate in continuing their parents' business, but business continuity is carried out naturally and there is support from the environment. This is different from Batik EB, where there was a conflict within the family due to Hisham's parents' decision to hand over EB's batik business to Hisham. However, a solution was immediately found so that it was back in good condition.